1987
DOI: 10.1128/jb.169.6.2624-2630.1987
|View full text |Cite
|
Sign up to set email alerts
|

Operator sequences of the aerobactin operon of plasmid ColV-K30 binding the ferric uptake regulation (fur) repressor

Abstract: The promoter region of the pColV-K30-encoded operon specifying biosynthesis and transport of the siderophore aerobactin was subjected to deletion analysis to determine the smallest DNA sequence affording iron regulation of a iucA'-'lacZ gene fusion. A 78-base-pair (bp) region containing the main (P1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
460
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 517 publications
(477 citation statements)
references
References 21 publications
15
460
2
Order By: Relevance
“…Under the aerobic growth conditions employed here, FNR is unlikely to be active [23] and will not contribute to soda regulation. We could detect no 'iron box' (GATAATGAT A ATCATTATC) for binding FUR [24] in the hmp promoter region. A third represser of sodA is Integration Host Factor (IHF), product of the himA gene [25].…”
Section: Induction Of Soda By Hmp Is Ihf-independentmentioning
confidence: 77%
“…Under the aerobic growth conditions employed here, FNR is unlikely to be active [23] and will not contribute to soda regulation. We could detect no 'iron box' (GATAATGAT A ATCATTATC) for binding FUR [24] in the hmp promoter region. A third represser of sodA is Integration Host Factor (IHF), product of the himA gene [25].…”
Section: Induction Of Soda By Hmp Is Ihf-independentmentioning
confidence: 77%
“…Exogenous regulatory signal(s) activate LemA, a membrane-bound sensor kinase, which in turn regulates the production of bacterial autoinducers that control the biosynthesis of antifungal metabolites like siderophore/antibiotics [24] and the transcription of iron-regulated gene is under the negative control of protein [repressor] with Fe 2+ as an essential co-repressor. Increase in the concentration of iron in cell cytoplasm cause iron toxicity to the cell [22,25]. 2+ in the intracellular control of siderophores synthesis and are responsible for repressing siderophore synthesis [26].…”
Section: Resultsmentioning
confidence: 99%
“…In its most basic state, Fur forms a dimer together with divalent cations, such as ferrous iron, and binds to a consensus sequence (the Fur box) that overlaps the promoters of iron-regulated genes to prevent their transcription. Recent studies indicate that in some organisms, Fur may also function as a positive regulator of gene transcription, together with iron (8,(9)(10)(11)(12)24), although the mechanism of iron activation by Fur is not well elucidated. Our recent studies of N. meningitidis group B, using a combination of microarray technology, computational analysis, and in vitro binding studies, revealed that a large number of genes are activated during growth in the presence of iron and that a number of these iron-activated genes have putative Fur-binding sequences to which Fur was demonstrated to bind (17).…”
mentioning
confidence: 99%